Significantly Raising the Cell Performance of Lithium Sulfur Battery via the Multifunctional Polyaniline Binder. (1st April 2017) - Gao, Hong; Lu, Qi; Yao, Yujie; Wang, Xianhong; Wang, Fosong
Abstract: Binder is critical component to maintain the cathode integrity in lithium-sulfur battery, but it is generally non-conductive. Here sulfuric acid doped polyaniline was successfully developed as conductive binder, which showed multifunctionality when used in Li-S battery cathode, i.e ., in addition to necessary adhesion function, it could trap polysulfide species to abate shuttling affect while provide good electrical conductivity. The unique adhesive behavior of conductive polyaniline was attributed to the sufficiently long polar chains consisting of amine salt, iminium and aromatic ring. Based on theoretical analysis, all the electrode components could be bound together by Van der Waals and electrostatic interactions even under very low polyaniline loading. Such low loading could form conductive polyaniline cobweb which helped the polyaniline binder to resist sulfur swelling while provide adequate channels for ion transportation. In an optimal condition, the polyaniline binder loading in cathode could be reduced to Ca . 2.0 wt%, and the sulfur loading in cathode increased by 11.0 wt% compared with that using common non-conductive binder. Compared with cathode employing common PVDF binder, the specific capacity using polyaniline binder increased by Ca. 104% and 74% at current density of 122 mA g −1 -sulfur and 610 mA g −1 -sulfur, respectively, which was mainly attributed to the stable conducting feature of polyaniline binder during the charging-discharging process, as reflected from low charge transfer resistance of 37 ohm for the cathode.